THE EFFECT OF LIQUIDITY, GOOD CORPORATE GOVERNANCE, AND COMPANY SIZE ON COMPANY’S FINANCIAL PERFORMANCE (STUDY IN THE PANDEMIC TIME OF COVID-19) - Febryanti Simon; Clarissa Maya Devi; Angelia Shavira Putri (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The purpose of this study is to determine and analyzed the impact of pandemic time of covid 19 to financial performance of company that can be analysed from 3 variable independent, such as: liquidity, good corporate governance, and company size. The research is in companies that listed in Indonesian Stock Exchange (IDX) during pandemic time of covid 19. The sampling technique used purposive sampling and the type of data uses is quantitative with regression analysis method. Based on the test results, it is concluded that institutional ownership has a significant effect on the company's financial performance. Besides having its own meaning, this research also has its own limitations. First, analysis only for Indonesia area (because researcher only took the sample only from companies that listed in IDX). If the sample of companies increases and different countries will give different result and analysis. Second, this research only analyzed the impact during second quarter during pandemic time, if time is extended for one year, will be give different result and supposed to be if the time extended, the result will give more implications. The research implication are as follows: For all high level management in companies, to strengthen decision making during pandemic time of covid 19 should be check and analyzed the financial statement of companies and can give more valuable interpretations analysis for all the user of financial statement.